Coronary artery size and origin imaging in children: a comparative study of MRI and trans-thoracic echocardiography. Issue 1 (December 2015) - Hussain, Tarique; Mathur, Sujeev; Peel, Sarah; Valverde, Israel; Bilska, Karolina; Henningsson, Markus; Botnar, Rene; Simpson, John; Greil, Gerald
Abstract Background The purpose of this study was to see how coronary magnetic resonance angiography (CMRA) compared to echocardiography for the detection of coronary artery origins and to compare CMRA measurements for coronary dimensions in children with published echocardiographic reference values. Methods Enrolled patients underwent dual cardiac phase CMRA and echocardiography under the same anesthetic. Echocardiographic measurements of the right coronary artery (RCA), left anterior descending (LAD) and left main (LM) were made. CMRA dimensions were assessed manually at the same points as the echocardiographic measurements. The number of proximal LAD branches imaged was also recorded in order to give an estimate of distal coronary tree visualization. Results Fifty patients (24 boys, mean age 4.0 years (range 18 days to 18 years)) underwent dual-phase CMRA. Coronary origins were identified in 47/50 cases for CMRA (remaining 3 were infants aged 3, 9 and 11 months). In comparison, origins were identified in 41/50 cases for echo (remaining were all older children). CMRA performed better than echocardiography in terms of distal visualization of the coronary tree (median 1 LAD branch vs. median 0;p  = 0.001). Bland-Altman plots show poor agreement between echocardiography and CMRA for coronary measurements. CMRA measurements did vary according to cardiac phase (systolic mean 1.90, s.d. 0.05 mm vs. diastolic mean 1.84, s.d. 0.05 mm;p  = 0.002). Conclusions Dual-phase CMRA has an excellent (94 %) success rate for the detection of coronary origins in children. Newborn infants remain challenging and echocardiography remains the accepted imaging modality for this age group. Echocardiographic reference ranges are not applicable to CMRA measurements as agreement was poor between modalities. Future coronary reference values, using any imaging modality, should quote the phase in which it was measured.